Tata Negara dalam Perspektif Fiqh Siyâsah - Syaiful Hidayat (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2013)
Dimensions of Islamic teachingsare verybroad and universal. Islamis notonly desirableas a means ofactivity ritualism but more than that, Islam has beenable to answer and becamethe foundation of social lifeis absolutely. One dimension of Islam it is the system of government of a country. Islam also offers concept and system of government based on religious values ??are sublime. State is a means to establish and enforce Islamic law to the public at large. Objective To achieve that the Islamic law should be organized formally in a state institution as practiced by Prophet Muhammad SAW and forwarded by the state in the context of the medina khulafâurrâshidîn.